The Impact of Forensic Accounting on Mitigating Tax Fraud in Nigeria: An Analysis of Current Trends and Organisational Implications - Paramole, Ibrahim Babatunde (Universitas Ratu Samban, 2025)
Financial crimes, particularly tax fraud, pose significant challenges to Nigeria's economic stability and public trust. Despite establishing regulatory frameworks and anti-corruption laws, the growing sophistication of fraud schemes has outpaced traditional auditing methods. This research explores the effectiveness of forensic accounting in detecting and preventing financial crimes in Nigeria. A case study approach was employed, involving in-depth analysis of specific instances of financial fraud and interviews with forensic accounting professionals to evaluate current practices and their impact on fraud detection. The findings indicate that while forensic accounting techniques, such as documentation review and financial statement analysis, significantly enhance fraud detection, notable gaps exist in stakeholder awareness, training and implementation. Additionally, the study highlights the necessity for improved collaboration among regulatory agencies and the adoption of advanced technologies like big data analytics to bolster forensic accounting efforts. In conclusion, the research emphasises the importance of integrating forensic accounting into existing financial practices to combat financial misconduct effectively. This study contributes valuable insights into the challenges and opportunities associated with forensic accounting in Nigeria, offering practical recommendations for stakeholders to refine their practices. Ultimately, it underscores the potential of forensic accounting as a crucial tool for promoting transparency and accountability in Nigeria's financial landscape.